Incident Record System (InReS) / Nurul Izah Md Salleh - Md Salleh, Nurul Izah (2017)
The purpose of this project is to identify the current process and problem faced by Polis Bantuan UiTMKT when record case reported by UiTMKT students. Incident Record System (InReS) classified all report case into several categories such as matrix, property, vehicle and pedestrian. Warning and suggestion action will be alert the using in certain situation. Development of InReS is due to several problems stated by Polis Bantuan. As the problem recognized, the solution to minimize the problem has been recognized by developing Incident Record System (InReS). To ensure the smoothness in developing appropriate development model and methodology is applied. Development process totally applied adapted waterfell methodology. Testing has been done by user and expert to test the functionality and the usability of the system The result will be evaluate and analyze. Comment and suggestion from expert used to improve the system so that the system developed can meet the whole requirement needed.